An investigation of factors that impact patients' subjective experience of nurse‐led clinics: a qualitative systematic review. Issue 1 (19th September 2014) - Jakimowicz, Samantha; Stirling, Christine; Duddle, Maree
<x xml:space="preserve">Abstract</x> Aims and objectives To systematically review the qualitative evidence on factors that affect the experience of patients attending nurse‐led clinics and compare with key elements of person‐centred care. Background As the number of nurse‐led clinics increases in response to health system needs, evaluation has focused on clinical outcomes and cost. Patient experiences are less researched and yet, they are an important influence on clinical outcomes and an indicator of person‐centred care. A detailed review of existing research in this area is needed. Design A systematic review of primary, qualitative literature was conducted using the Joanna Briggs Institute methodology of meta‐aggregation. Methods Published research from 1990–2012 was located using CINAHL, PubMed, Medline and PsycINFO. Reference lists were searched and analysed. Two reviewers assessed the papers for methodological quality using instruments from the Joanna Briggs Institute to critically appraise, extract data and meta‐aggregate findings. Results Eleven studies met all inclusion criteria. Three meta‐synthesis statements were derived from 46 findings aggregated to nine categories. The key themes relating to establishment of a therapeutic relationship, effective communication, and clinical skills and collaboration mapped closely to the person‐centred care framework. Conclusion Concepts central to person‐centred care proved to be factors impacting patients' subjective experience. Further research is warranted to meet the challenge to transform the key concepts of the person‐centred care model into everyday nursing practice. Relevance to clinical practice Knowledge of patients' feelings and the importance of person‐centred, individualised care may contribute to development of future training and re‐training programs in basic nursing skills. This is significant in that it contributes to future positive patient experience.